Age estimation: Cameriere's open apices methodology accuracy on a southeast Brazilian sample. (August 2018) - Mazzilli, Luiz Eugenio Nigro; Melani, Rodolfo Francisco Haltenhoff; Lascala, Cesar Angelo; Palacio, Luz Andrea Velandia; Cameriere, Roberto
Abstract: Age estimation plays an important role in clinical and forensic dentistry. Cameriere's 2007 open apices method for age estimation was applied in a sample of 612 digital panoramic orthopantomographs from Brazilian subadult individuals of known age and sex. The sample was composed of 290 males and 322 females individuals aged between four and 16 years of age from São Paulo metropolitan area who had undertaken radiographs for clinical purposes. Participant's ethnicity data was not available. An open code computer-aided drafting software (ImageJ) was used to measure the variables according to the author's published guidelines. Subjects' age was firstly estimated under the application of the European formula (2007) showing under-estimation (−1.24yr). On the other hand, the linear regression analysis modeled for this specific population was able to explain 91.2% of the chronological age variation with a standard error of 0.91yr. Residual analyses confirmed independent errors and a normal distribution. In conclusion, the present results support Cameriere's method for age estimation in Brazilian subadults to be a reliable method, although correlations may vary between specific groups and, hence, specific formulae may be useful for an accurate prediction. Highlights: A Southeast Brazilian sample specific formula for Camerieres' open apices methodology was developed. The developed formula revealed a improved accuracy over Cameriere's European formula. The new model explained 91.2% of the chronological age variation (S.E. = .90 years).